Thirty-five years of Tropical biology: a quantitative history - Monge-Nájera, Julian; Díaz, Lizeth (Revista de Biología Tropical, 1988)
Citation indices are unappropriated measures of scientific output and impact. For that reason, nonparametric statistics were preferred to analyze 35 years of publication on Tropical biology in the Revista de Biología Tropical. The most frequent subjects are animal taxonomy, human biology -including medicine- ecology and animal behavior. Botany papers are less frequent and mainly deal with morphology and taxonomy. Applied studies are not predominant. In that period, only one case of unethical experimentation with humans was discovered in a paper of Mexican origin. The proportion of foreign institutions publishing in the journal has increased from 23% (1953-1963) to 50% in the last decade; similarly, the number of studies done in the Neotropics is on the rise. English and Spanish are equally frequent, although English is the basic language of ethology and evolution and Spanish predominantes in papers on animal morphology and parasitology. Most Costa Rican authors publish in Spanish, in contrast with many of their Latin American colleages. In recent years, there is a tendency to publish shorter papers written by more than one author. The Revista de Biología Tropical, covered by 18 data bases, accounts for most exchanges and sales in the Universidad de Costa Rica and has worldwide distribution.